Antibacterial activity and characterization of ZnO and Ag-doped ZnO nanoparticles fabricated using Leucophyllum frutescens leaf extract - Asma Umer; Hira Hameed; Muhammad T. Sarwar; Abdul Sammad A. K. Shirwany; Zain ul Abidin; Amna Farooq; Muhammad Taimoor; Aneeqa Naveed; Kanwal Majeed (One Health Microbiology & Infection, 2026)
Globally, there has been considerable interest in the environmentally benign production of transition-metal nanoparticles. This study describes the synthesis of ZnO and Ag-doped ZnO nanoparticles using the leaf extract of Leucophyllum frutescens via a simple green method. The synthesized nanoparticles were characterized by Ultraviolet-Visible (UV-Vis) spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy, X-ray diffraction (XRD), Transmission electron microscopy (TEM), and scanning electron microscopy (SEM). TEM analysis showed that the crystallites were spherical and polyhedral, highly agglomerated, and had interplanar diameters ranging from 0.2005 to 0.2625 nm. The antimicrobial efficacy of the developed ZnO and Ag/ZnO nanoparticles at concentrations of 3%, 5%, and 7% was evaluated against human pathogens, including Bacillus cereus, Staphylococcus aureus, Salmonella typhi, and Escherichia coli. The synthesized ZnO and Ag-doped ZnO nanoparticles showed a characteristic absorption band in the UV region, confirming successful formation of ZnO-based semiconductor nanostructures and supporting their antibacterial activity against the tested pathogens. The results revealed that at 7% Ag-doping, Ag-doped ZnO nanoparticles exhibited greater antibacterial efficacy than pure ZnO nanoparticles, with the largest inhibition zones observed against S. aureus (11 ± 3.0 mm) and B. cereus (12.45 ± 0.57 mm). Overall, this plant-mediated synthesis of Ag-doped ZnO nanoparticles offers a promising route for developing enhanced antibacterial agents and highlights a green, cost-effective, and sustainable method for producing ZnO and Ag-doped ZnO nanoparticles, with various applications for future exploration.